ASSOCIATION BETWEEN HIV AWARENESS FACTORS, HEALTH FACILITY CHARACTERISTICS AND RISKY SEXUAL BEHAVIOUR AMONG YOUNG WOMEN IN ZOMBA DISTRICT, MALAWI. Issue 6 (30th January 2018) - Ward-Peterson, Melissa; Fennie, Kristopher; Baird, Sarah; Coxe, Stefany; Trepka, Mary Jo; Madhivanan, Purnima
Summary: The objective of this study was to examine the association between multilevel factors related to HIV awareness and risky sexual behaviour among young women in Zomba district, Malawi. Secondary analyses of the Schooling, Income, and Health Risk (SIHR) study were undertaken. Four outcomes related to risky sexual behaviour were examined among young women: if participants had ever had sex, consistent condom use and two scores measuring risk related to partner history and age during sexual activity. Independent variables included individual-level factors such as education and rural/urban residence, as well as higher-level factors such as household's highest level of education and health facility characteristics. Regression models with cluster-robust standard errors and multilevel regression models were used to estimate associations; analyses were stratified into two strata by school enrolment status, i.e. whether the women were in school ( N =1407) or had dropped out of school ( N =407) at baseline of the SIHR study. For both strata, increasing age and residing within 16 km of an urban centre ('near rural' residence) increased the odds of ever having sex; lower educational achievement was associated with lower age during sexual activity. A history of pregnancy was associated with lower odds of condom use and riskier partner history. For women in school at baseline, lower household education was associated with higher odds of ever having sex (OR=1.48; 95% CI: 1.06, 2.07); near-rural and far-rural (≤16 km and >16km from urban centre, respectively) residence were associated with decreased odds of condom use (OR=0.47; 95% CI: 0.28, 0.78; and OR=0.27; 95% CI: 0.11, 0.65, respectively). For those not in school at baseline, lower household education was associated with lower age during sexual activity ( β =0.31, 95% CI: 0.05, 0.58). Also for women not in school, the use of private or non-governmental health facilities was associated with decreased odds of condom use (OR=0.51, 95% CI: 0.39, 0.67) and higher age during sexual activity ( β =−0.30, 95 % CI: −0.52, −0.09). While individual factors were associated with risky sexual behaviour in both strata, contextual factors differed.